Pengaruh kebijakan hutang dan kebijakan dividen terhadap nilai perusahaan yang tercatat pada Indeks LQ 45 Bursa Efek Indonesia Periode 2015-2019 - Chan, Beby Fadillah; Maulana, Zefri; Kamal, Safwan (Jurnal Investasi Islam, 2022)
This study aims to determine the effect of debt policy (DER) and dividend policy (DPR) partially and simultaneously on firm value (PBV) listed on the LQ 45 index of the Indonesian stock exchange for the 2015-2019 period. The data used is secondary data, based on financial statements on the Indonesian stock exchange. The data analysis in this study is multiple regression analysis, using normality test, multicollinearity, heteroscedasticity test, t test, f test, and coefficient of determination test through SPSS. The results of this study indicate that partially debt policy has no effect on firm value with a t value of -0.389 with a significance of 0.698 > 0.5 (0.000 < 0.05), dividend policy proxied by the DPR has a positive and significant effect on firm value. proxied by PBV with a t-count value of 3.343 and a significance <0.05. Meanwhile, simultaneous hypothesis testing has a positive and significant effect on firm value, this is indicated by the calculated F value of 5.825 and a significance value of 0.04 which is <0.05. The value of R2 in this study is 0.070, this indicates that the firm value is influenced by debt policy and dividend policy by 7% while the remaining 93% is influenced by variables outside this study.